Impact of the menstrual cycle and barriers to football and futsal performance in Portuguese players: a survey-based cross-sectional study - Santos, C.; Lopes, M.; Brito, J.; Kryger, K. O.; Wilke, C.; Travassos, B. (Frontiers in Psychology, 2025)
Introduction: The objective of this study was to investigate the perceived impact of the different phases of the menstrual cycle on football and futsal participation and identify barriers that may limit the performance and participation of Portuguese female players across competition levels.